(untitled) (International Journal of Advanced Research in Computer Science, 2017)
Time is the most important feature that counts for an executing process. Nowadays, applications are more focused to reduce the computational time and thus to increase the speed. Therefore, there is a need to redesign the fundamental algorithms especially for searching methods to achieve this objective. Targeting this, approach of memorization is proposed in this paper to optimize the time of searching during execution. It is an optimization technique used to eliminate re-execution time for pure function. A novel approach of memoized Quadratic Search Algorithm is presented in this paper. Results show remarkable improvement in the performance in terms of time leading to achieve the said objective. This will help to optimize the time in other respective areas of computation processes. Keywords: Binary Search, Quadratic Search, Optimization, Memoization, Execution Time.